Residual method of property valuation - Skarzyński, Andrzej (Technological and Economic Development of Economy, 2006)
In the paper the residual method as one of the methods used for property valuation by mixed approach is presented. The paper contains the description of the most often used applications of the residual method and two examples of the practical usage of this method. The first example relates to the valuation of a family house being built for the purpose of obtaining a mortage loan to complete construction work. The second example concerns the valuation of an office building considered for purchasing by a potential buyer. The paper ends with the conclusions concerning the conditions of property valuation.Nekilnojamojo turto vertinimas likutinės vertės metoduSantrauka. Straipsnyje nagrinėjamas vienas mišraus tipo likutinės vertės metodas nekilnojamajam turtui vertinti. Aprašyti šio metodo dažniausiai pasitaikantys atvejai ir pateikti du praktiniai metodo taikymo pavyzdžiai. Pirmajame pavyzdyje aprašytas individualaus gyvenamojo namo įvertinimo atvejis, kai norima paimti paskolą pradėtiems statybos darbams baigti. Antrajame pavyzdyje įvertinamas biuro pastatas, kuriam ieškoma potencialaus pirkėjo. Straipsnio išvadose aptariami kai kurie nekilnojamojo turto vertinimo aspektai.Reikšminiai žodžiai: nekilnojamojo turto vertinimas, požiūriai, vertinimo metodai ir technika.First Published Online: 21 Oct 2010